2015
DOI: 10.1208/s12248-015-9837-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Phospholipid-Based Complex of Standardized Centella Extract (SCE) for the Enhanced Delivery of Phytoconstituents

Abstract: Abstract. In the present study, a phospholipid-based complex of standardized Centella extract (SCE) was developed with a goal of improving the bioavailability of its phytoconstituents. The SCE-phospholipid complex was prepared by solvent evaporation method and characterized for its physicochemical and functional properties. Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), photomicroscopy, and powder x-ray diffraction (PXRD) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…In a previous study [46] it was reported that there was an increase in the vesicle size of avanafil invasomes with increasing Phospholipon concentration. In general, the results observed in our study were very much consistent with previously reported vesicular systems [47]. Three-dimensional (3D) response surface plots for the effect of the investigated variables on the vesicle size ( Figure 3) illustrate that ICA:Phospholipon ® 90H molar ratio exhibited the most significant effect on vesicle size.…”
Section: Influence Of Variables On Vesicle Sizesupporting
confidence: 91%
“…In a previous study [46] it was reported that there was an increase in the vesicle size of avanafil invasomes with increasing Phospholipon concentration. In general, the results observed in our study were very much consistent with previously reported vesicular systems [47]. Three-dimensional (3D) response surface plots for the effect of the investigated variables on the vesicle size ( Figure 3) illustrate that ICA:Phospholipon ® 90H molar ratio exhibited the most significant effect on vesicle size.…”
Section: Influence Of Variables On Vesicle Sizesupporting
confidence: 91%
“…These approaches include, and are not limited to salt formation, solid-dispersions, prodrug formation, complexation, particle size modifications, micellization, micro-and nano-technological approaches such as micro-emulsions, micro-suspensions, nanoemulsions, nano-suspensions, solid-lipid nanoparticles, etc. [10][11][12][13][14][15][16][17][18][19][20][21][22] The term solid dispersions (SD) has been described earlier as a dispersion of one or more Active Pharmaceutical Ingredient (API) in an inert carrier or a matrix in solid state, prepared by solvent, melting or solvent-melting method. 23 The API in a SD can be dispersed as separate molecules, amorphous particles or crystalline particles; while the carrier can be in a crystalline or amorphous state.…”
Section: Introductionmentioning
confidence: 99%
“…It is a tropical plant from the Apiaceae family and is widely distributed in Southeast Asian countries, such as India, China, Sri Lanka, Malaysia, and Indonesia, as well as South Africa and Madagascar (Orhan, 2012). The major chemical constituents found in C. asiatica are triterpenoid derivatives, such as asiatic acid, madecassic acid, asiaticoside, and flavonoids (Saoji et al, 2016;Sari et al, 2014;Vasavi, Arun, & Rekha, 2016). This plant has been widely used in Ayurvedic, African, and Chinese traditional medicine (Giribabu, Srinivasarao, Swapna Rekha, Muniandy, & Salleh, 2014;Vasavi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%